INTEGRASI BUDAYA ISLAM DALAM PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI KEAGAMAAN ISLAM (PTKI) - Salu, Herlina Tandi; Hanisy, Asmad; Rizal, Syaiful (International Conference on Humanity Education and Society (ICHES), 2025)
The integration of Islamic culture in Islamic religious education at Islamic Higher Education Institutions (PTKI), particularly at Universitas Islam KH. Achmad Muzakki Syah, reflects an effort to harmonize Islamic values with the local context. This research explores the methods and practices used to integrate Islamic teachings into the curriculum, as well as their impact on the character development of students. With an approach that emphasizes local wisdom and local cultural traditions, Islamic education at this university focuses not only on theoretical aspects but also on the application of Islamic values in daily life. The research findings indicate that this integration positively contributes to the development of tolerance, ethics, and social concern among students, thereby creating a generation that is not only academically intelligent but also has a strong commitment to Islamic values and local culture. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis. The results show that Universitas Islam KH. Achmad Muzakki Syah Jember has successfully integrated Islamic culture into Islamic religious education in several ways, including the course "Tarbiyatul Manaqib," which is the result of the integration of values, teachings, and practices of dzikir manaqib into the curriculum of the Islamic Education Study Program at the Faculty of Tarbiyah. Overall, this research emphasizes that the integration of Islamic culture in Islamic religious education at this university has a positive impact on the character and personality development of students, as well as strengthening the relationship between Islamic teachings and local culture.